Two Step and Direct Fermentation in the Production of Ethanol from Starch: A Short Review - Endah Retno Dyartanti; Margono Margono; Anisa Raditya Nurohmah; Shofirul Sholikhatun Nisa; Novan Riantosa (Equilibrium Journal of Chemical Engineering, 2020)
Abstract.  Ethanol as a renewable fuel has been widely produced in various countries. One source of raw material for producing ethanol is starch. The process of producing ethanol from starch needs to be pretreated so that starch molecules can split into smaller ones. However, this process requires pre-treatment which will expensive more than ethanol from sugar. There are two types of pretreatment i.e. two-step ethanol production and direct fermentation. There is two kind of hydrolysis, acid hydrolysis, and enzymatic hydrolysis. Two-step ethanol production is a conventional method that separates pretreatment and fermentation process, while direct fermentation is the direct production of starch into ethanol using recombinant yeast that co-produces enzymes such as amylose and glucoamylase. Two-step ethanol production has the advantage of high yield but needs high cost whereas, direct fermentation has the advantage of low-cost production but needs longer time. Common starch to ethanol production consists of two stages, namely hydrolysis of raw materials into glucose and fermentation into ethanol. Both of these processes can be run on average at temperatures of 30-80oC with a pH range of 4-6 and varying time intervals. The enzyme used depends on the source of the starch, but the most commonly used is Saccharomyces cerevisiae.Keywords: Ethanol, starch, pre-treatment